(untitled) (Iranian Journal of Kidney Diseases, 2018)
Introduction. Disturbances of lipid metabolism has been reported in nephrotic syndrome (NS) and may predispose to atherosclerosis. This study aimed to investigate the correlation between cardiovascular risk factors and carotid intima-media thickness (CIMT) and brachial artery flow-mediated dilatation in patients with idiopathic NS. Materials and methods. This case-control study included 31 patients with NS and 31 healthy individuals as the control group. All patients were subjected to full clinical examination; laboratory investigations in the form of lipid profile, kidney function tests, serum protein, serum albumin, C-reactive protein, and ferritin; carotid ultrasonography, and brachial artery flow-mediated dilatation. Results. Serum cholesterol, low-density lipoprotein cholesterol, and triglyceride levels was significantly higher in the case group than the control group. High-density lipoprotein cholesterol and albumin levels were significantly lower in the case group. The absolute change in brachial artery diameter was significantly lower in the case group than that of the control group. Proportionate change in brachial artery diameter was significantly lower in the case group than that of the control group. Common carotid artery CIMT in the case group was significantly higher than that of the controls. Lastly, there were significant increases in weight and body mass index in the relapse group than the remission group. Conclusions. Patients with NS are more prone to atherosclerosis and vascular changes; CIMT was thicker in nephrotic children compared to the controls. The significantly abnormal values of flow-mediated dilatation in children with NS suggests an ongoing process of endothelial dysfunction.